Understanding lung cancer molecular subtypes. (July 2014) - Pender, Alexandra; Popat, Sanjay
In-depth analysis of the cancer genome has revolutionized our approach to treating solid organ malignancies. Therapeutic strategies are now driven by tumor genotyping and the identification of drug targets. Non-small-cell lung cancer is a prime example of a tumor in which specific disease subtypes are now defined by molecular genotype, rendering a homogenous approach to lung cancer management inappropriate. Herein, we review molecular characterization of non-small-cell lung cancer to date, its clinical and therapeutic impact and data that underpin routine use of molecular targeted therapy for specific tumor genotypes. We discuss molecular mechanisms of acquired drug resistance and potential therapeutic strategies to overcome this, as well as identifying genotype-directed approaches to treating newly identified somatic aberrations in development.